NOVEL SIRKUS POHON KARYA ANDREA HIRATA SEBAGAI MATERI AJAR SASTRA SMP: SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER - Muhammad Abdul Azis; Andayani Andayani; Suyitno Suyitno (Universitas Sebelas Maret, 2019)
The aim of the research are describe (1) influence of the author background in the novel Sirkus Pohon by Andrea Hirata; (2) readers response to novel Sirkus Pohon by Andrea Hirata; (3) character education value of the novel Sirkus Pohon by Andrea Hirata: (4) relevance novel Sirkus Pohon by Andrea Hirata with literature education in junior high school.This research is qualitative descriptive research and the method used contents analysis. The research approach used sociological approach of literature and literary reception. The results are (1) influences of the author backgrouds which are social culture, family, education and profesion, and author religion; (2) the response of readers of the novel Sirkus Pohoninclude ideal readers dan ordinary readers. The ideal readers category argue that the novel contains many lessons that can be learned for the readers so its worth reading. Theordinary readers state that the novel is a good and interesting novel. (3) value character education of novel Sirkus Pohon by Andrea Hirata are religious, hardwork, sosial care, and responsible: (4) relevance novel Sirkus Pohon by Andrea Hirata with learning literature in junior high school are comformity guidelines for evaluating enrichment tekxbooks from department of education and culture Indonesia.